CRIMINAL LAW FUNCTION OF POLICE AS THE QUINTESSENCE OF CRIME PREVENTION – ESSENCE AND DEVELOPMENT PERSPECTIVES - Feldmanis, Ainars (Administrative and Criminal Justice, 2016)
The criminal law function carried out by the police is one of the most visible aspects of crime prevention. In the context of transformation of Latvian legal system, it is purposeful to structure this function using both the objectives of police as seen in regulatory enactments, as well as the methods used in order to achieve these objectives. This allows you to detect problems in the police activities and to choose solutions for improving these activities.